Ginsenoside Rc Ameliorates Endothelial Insulin Resistance via Upregulation of Angiotensin-Converting Enzyme 2 - Wang, Yaozhen; Fu, Wenwen; Xue, Yan; Lu, Zeyuan; Li, Yuangeng; Yu, Ping; Yu, Xiaofeng; Xu, Huali; Sui, Dayun (Frontiers in Pharmacology, 2021)
Type 2 diabetes mellitus (T2DM) is a major health concern which may cause cardiovascular complications. Insulin resistance (IR), regarded as a hallmark of T2DM, is characterized by endothelial dysfunction. Ginsenoside Rc is one of the main protopanaxadiol-type saponins with relatively less research on it. Despite researches confirming the potent anti-inflammatory and antioxidant activities of ginsenoside Rc, the potential benefits of ginsenoside Rc against vascular complications have not been explored. In the present study, we investigated the effects of ginsenoside Rc on endothelial IR and endothelial dysfunction with its underlying mechanisms using high glucose (HG) cultured human umbilical vein endothelial cells (HUVECs) in vitro and a type 2 diabetic model of db/db mice in vivo. The results showed that ginsenoside Rc corrected the imbalance of vasomotor factors, reduced the production of Ang (angiotensin) II and activated angiotensin converting enzyme 2 (ACE2)/Ang-(1-7)/Mas axis in HG-treated HUVECs. Besides, ginsenoside Rc improved the impaired insulin signaling pathway, repressed oxidative stress and inflammatory pathways which constitute key factors leading to IR. Interestingly, the effects of ginsenoside Rc on HG-induced HUVECs were abolished by the selective ACE2 inhibitor MLN-4760. Furthermore, ginsenoside Rc exhibited anti-inflammatory as well as anti-oxidant properties and ameliorated endothelial dysfunction via upregulation of ACE2 in db/db mice, which were confirmed by the application of MLN-4760. In conclusion, our findings reveal a novel action of ginsenoside Rc and demonstrat that ginsenoside Rc ameliorated endothelial IR and endothelial dysfunction , at least in part, via upregulation of ACE2 and holds promise for the treatment of diabetic vascular complications.